Towards a Data-Centric Distributed Simulation Framework for the Energy Domain - Seiwerth, Corinna; Niebisch, Michael; German, Reinhard (1. NFDI4Energy Conference, 2024)
Existing simulation tools from the energy domain are often limited to specific problems in the energy sector. Co-simulation frameworks enable the combination of these models and, thus, a more realistic simulation of the energy domain. This paper analyzes some co-simulation frameworks from the energy domain by evaluating them according to specific criteria. Since none of the presented frameworks fulfills all the criteria, we then present a data-centric distributed simulation framework and how we extend it for the energy domain.<br
Keywords: Co-Simulation; Data-Centric Distributed Simulation; Energy System Mod- eling